Meningkatkan Derajat Kesehatan Melalui Pendekatan Biopsikospiritual Pada Kelompok Lansia - Aneng Yuningsih; Tyas Prayesti; Nandang Wahyu (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: as we get older, the aging process continues and causes various kinds of changes. The body will experience changes in structure and physiology. There are 4 changes due to the aging process, namely physical and functional changes, mental changes, psychosocial changes and spiritual changes. To survive the decline in body function, the elderly must be able to continue to adapt to the situation. Objective: To improve the level of health through a biopsychospiritual approach in the elderly group with a total of 146 activity participants in the active elderly category. Method: Implementation of community service is carried out through stages: Preparation, Socialization, Implementation of Activities (Explanation of material, Simulation and Evaluation) and Closing. Results: Based on the data above, it can be seen that the problems experienced by the activity participants were high blood pressure, dizziness, pain in the joints, pain in the stomach and solar plexus area, mild anxiety and sleep disturbances and a feeling of hopelessness due to the pain they complained about. Furthermore, the evaluation results at the end of the activity showed an increase in understanding of the material presented by the presenters. With an average increase of 50%. This community service activity is documented in the pictures below. Conclusion: Based on the results of the evaluation of Community Service activities, the picture of understanding about efforts to improve health status through a biopsychospiritual approach in the elderly group through education and simulation has increased quite significantly.